Digital ringgit: a new digital currency with traditional attributes - Abu, Nur Azman; Kedah, Zulkarnain; Rahardja, Untung; Sibarani, Blasius Erik; Kosasi, Sandy; Dewi, Susanti; Fadli, Ihya Syihabul (2023)
The development of central bank digital currencies (CBDCs) is underway around the world. They are essential for modernizing the national financial network. While most countries are calling for proof of concept for CBDCs, central banks have taken various approaches to designing CBDCs and are progressing their research and development efforts. Independence. Without CBDCs, private digital currencies will increasingly be dominated by non-financial companies. The appeal and instant recognition of paper money has been established for over 100 years. It is designed to have the appearance of a sovereign currency. Even if there is a serial number written on it, the carrier is still considered the owner without any conditions. Launching a CBDC poses some major challenges. The first technical challenge was to provide an offline device for trading digital currencies. The second technical challenge is called the double spending problem. The third technical challenge is measuring and controlling the velocity of money flow in digital transactions. This project will propose and develop a digital ringgit in light of these challenges. A digital Malaysian ringgit (DRM) note can be uniquely assigned to multiple session numbers. Here there is a need for a blockchain on the digital ringgit. Digital currency initiatives will bring significant benefits to developing economies; hence the cashless system will be useful in the fight against corruption and money laundering. Eventually, the digital ringgit will provide a control mechanism to a central bank, such as Bank Negara Malaysia, on its monetary velocity and growth of electronic money in a cashless society. A digital ringgit has an enormous potential to spur a financial cycle in Malaysia